2020
DOI: 10.3390/microorganisms8101481
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences of High-Density Agricultural Animal Operation on Human Forearm Skin Microflora

Abstract: The human forearm skin microbiome ecosystem contains rich and diverse microbes, which are influenced by environmental exposures. The microbial representatives can be exchanged between human and environment, specifically animals, by which they share certain or similar epidermal microbes. Livestock and poultry are the microbial sources that are associated with the transmission of community-based pathogenic infections. Here, in this study, we proposed investigating the environmental influences introduced by lives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The reductions in Corynebacterium and Cutibacterium numbers and increases in Pseudomonas and Acinetobacter amounts were observed primarily in farmworkers who were in contact with various species of farm animals [ 77 ].…”
Section: Living and Working Environmentmentioning
confidence: 99%
“…The reductions in Corynebacterium and Cutibacterium numbers and increases in Pseudomonas and Acinetobacter amounts were observed primarily in farmworkers who were in contact with various species of farm animals [ 77 ].…”
Section: Living and Working Environmentmentioning
confidence: 99%
“…Dataset processing was performed in accordance with the method previously described [21,22]. The raw sequence dataset was demultiplexed using BCL2FastQ and the PhiX sequence was removed using DeconSeq.…”
Section: Metagenomic Dataset Processingmentioning
confidence: 99%
“…Peng et al found significantly higher levels of Proteobacteria (Pseudomonas and Acinetobacter, p < 0.05) but lower Actinobacteria (Corynebacterium and Propionibacterium, p < 0.05) on fore-arm skin microbiota of farmworkers. Frequent farm animal operations also demonstrated a reduction in Staphylococcus and Streptococcus [51]. Only one study analyzed gender and age-related differences in animal-exposed workers' microbiota.…”
Section: Tools For Microbiota Sampling and Analysismentioning
confidence: 99%